2014
DOI: 10.14503/thij-13-3405
|View full text |Cite
|
Sign up to set email alerts
|

Penetrating Nail-Gun Injury of the Heart Managed by Adenosine-Induced Asystole in the Absence of a Heart-Lung Machine

Abstract: During his work, an 18-year-old carpenter-in-training overbalanced and shot himself in the left median thorax with a nail gun. The patient was delivered to our thoracic surgery unit with a tentative diagnosis of penetrating lung trauma. An emergent computed tomogram showed a heart-penetrating nail injury. The patient was taken to the operating room, where he underwent emergency surgery that included sternotomy, pericardiotomy, extraction of the nail, and trauma treatment of the heart injury. The surgery was pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 25 publications
(58 reference statements)
0
15
0
Order By: Relevance
“…can lead to an extension of the defect or to an accidental closure of a coronary artery. In two of our other cases with penetrating cardiac trauma, the heart could be shut down with a bolus-injection of adenosine to achieve a safe primary closure [26,27]. In our current case the injection of adenosine did not lead to the desired reaction.…”
Section: Emergency Surgerymentioning
confidence: 61%
See 1 more Smart Citation
“…can lead to an extension of the defect or to an accidental closure of a coronary artery. In two of our other cases with penetrating cardiac trauma, the heart could be shut down with a bolus-injection of adenosine to achieve a safe primary closure [26,27]. In our current case the injection of adenosine did not lead to the desired reaction.…”
Section: Emergency Surgerymentioning
confidence: 61%
“…In our current case the injection of adenosine did not lead to the desired reaction. In special cardiac injury patterns the bolus-injection of adenosine is a therapeutic option [26][27][28][29]. Alternatively, a Forgatyor a Foley-catheter can be placed for temporary defect occlusion [30][31][32][33][34].…”
Section: Emergency Surgerymentioning
confidence: 99%
“…For example, adenosine could decrease the superoxide anion produced by polymorphonuclear leukocytes (PMNs) through the adenosine A2 receptor. 22 Adenosine signaling based on adenosine receptor induced by Caffeine could partially extend the life span of C. elegans. 23 Similarly, Peralta et al 24 reported that the protective effect of adenosine could be a result of an increase in extracellular adenosine in ischemic preconditioning.…”
Section: Discussionmentioning
confidence: 99%
“…With a 16 Charrière urinary catheter up to 250 ml/minute can be administrated. The intravenous administration of adenosine (Adrekar ® : 0,15–0,30 mg/kg KG) leads, through to a short block of the AV (atrioventricular) node, to an asystole, which simplifies the treatment of heart injuries [ 19 ], [ 21 ].…”
Section: Discussionmentioning
confidence: 99%